2005
DOI: 10.1097/01.mcg.0000165705.74079.fc
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathologic Study of Primary Adenosquamous Carcinoma of the Liver

Abstract: The current study highlights the prognostic factors of ASC of the liver, showing that the prognosis for patients with ASC is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
(33 reference statements)
0
25
0
Order By: Relevance
“…Adenosquamous cholangiocarcinoma (ASC) is a rare variant of cholangiocarcinoma, which was first described by Barr and Hancock in 1975 [11] and consists of malignant glandular and squamous components. Tumor cells have both mucin-producing glandular structures as in adenocarcinoma and irregularly shaped solid nests of polygonal cells with distinct cellular borders, eosinophilic cytoplasm, varying degrees of keratinization, and intercellular bridges as in squamous cell cancer [12][13] . Cholangiocarcinoma with squamous features have been previously described as ASC but also as mucoepidermoid carcinoma (mucus-producing cells and squamoid cells without keratin formation) and adenoacanthoma (squamous metaplasia) [6,14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosquamous cholangiocarcinoma (ASC) is a rare variant of cholangiocarcinoma, which was first described by Barr and Hancock in 1975 [11] and consists of malignant glandular and squamous components. Tumor cells have both mucin-producing glandular structures as in adenocarcinoma and irregularly shaped solid nests of polygonal cells with distinct cellular borders, eosinophilic cytoplasm, varying degrees of keratinization, and intercellular bridges as in squamous cell cancer [12][13] . Cholangiocarcinoma with squamous features have been previously described as ASC but also as mucoepidermoid carcinoma (mucus-producing cells and squamoid cells without keratin formation) and adenoacanthoma (squamous metaplasia) [6,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiocarcinoma with squamous features have been previously described as ASC but also as mucoepidermoid carcinoma (mucus-producing cells and squamoid cells without keratin formation) and adenoacanthoma (squamous metaplasia) [6,14] . The prognosis of ASC is extremely poor even with surgery and most patients are not candidates for surgery and chemotherapy at presentation [2,6,12] . Nakajima and Kondo [2] evaluated 11 patients with ASC and compared their prognosis with 82 cholangiocarcinoma patients with adenocarcinoma features and found that the mean overall survival was four months in ASC patients versus 6.9 months in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…7 The mean survival of these 34 cases was 8.7 months. Multivariate analysis revealed that lymph node metastasis and the elevation of total bilirubin were associated with poor survival after surgery, and lymph node metastasis, intra-hepatic metastasis, location of tumor in the right lobe, and the pathologic stage were significant factors for all cases.…”
Section: Discussionmentioning
confidence: 99%
“…ASC is a rare subtype of cholangiocarcinoma with more aggressive clinical and pathological features than other cholangiocarcinomas, and the prognosis of patients with hepatic ASC is extremely poor. Kobayashi et al [6] reported a mean survival time for patients with hepatic ASC of 8.7 months, and the overall 1-, 2-, and 3-year survival rates after surgery were 38.5, 16.2, and 10.8%, respectively. Uenishi et al [15] reported a 1-year survival rate for intrahepatic cholangiocarcinoma of 68%, indicating that the prognosis of patients with primary hepatic ASC was poorer than that of patients with the common type of hepatic cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…ASC contains both adenocarcinoma (AC) and squamous cell carcinoma (SCC) components, tends to present more aggressive clinicopathologic features, and has a poorer prognosis than other cholangiocarcinomas [6,7] . Barr and Hancock [8] first reported a case of primary hepatic ASC in 1975, since when several cases of histologically defined primary hepatic ASC have been reported in the literature [3, [9][10][11][12] ; however, none have been reported in patients with PSC.…”
mentioning
confidence: 99%